2014
DOI: 10.1146/annurev-ento-011613-162104
|View full text |Cite
|
Sign up to set email alerts
|

Response of Native Insect Communities to Invasive Plants

Abstract: Invasive plants can disrupt a range of trophic interactions in native communities. As a novel resource they can affect the performance of native insect herbivores and their natural enemies such as parasitoids and predators, and this can lead to host shifts of these herbivores and natural enemies. Through the release of volatile compounds, and by changing the chemical complexity of the habitat, invasive plants can also affect the behavior of native insects such as herbivores, parasitoids, and pollinators. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
200
5
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(226 citation statements)
references
References 153 publications
(176 reference statements)
8
200
5
3
Order By: Relevance
“…When repeated regularly, these management techniques cause overall diminishment of the variety of floral resources, and of the complexity of habitat required for the accumulation of nesting substrates Dixon 2009). In addition, episodic mowing on transmission line easements favors invasive plants, which can sometimes be problematic for native wildlife (Drake et al 2016;Freeman et al 2014;Bezemer et al 2014). One management strategy currently being explored by transmission companies throughout the US could potentially mitigate both problems.…”
Section: Introductionmentioning
confidence: 99%
“…When repeated regularly, these management techniques cause overall diminishment of the variety of floral resources, and of the complexity of habitat required for the accumulation of nesting substrates Dixon 2009). In addition, episodic mowing on transmission line easements favors invasive plants, which can sometimes be problematic for native wildlife (Drake et al 2016;Freeman et al 2014;Bezemer et al 2014). One management strategy currently being explored by transmission companies throughout the US could potentially mitigate both problems.…”
Section: Introductionmentioning
confidence: 99%
“…shown a negative impact of neophytes on insects (Tallamy 2004;Casagrande and Dacey 2007;Keeler and Chew 2008;Tallamy et al 2010;Fortuna et al 2013), which is confirmed by meta-analyses showing that non-invaded habitats, in comparison to habitats with a high proportion of alien species, had higher total abundance and taxonomic richness of arthropods (Bezemer et al 2014;van Hengstum et al 2014;Litt et al 2014). In situations where the optimal host is a rare species or there is high competition for food, the cost of feeding on the optimal host may be large enough for an insect that it favours the strategy of increasing the number of potential host plants by utilising a new species (Mayhew 1997).…”
mentioning
confidence: 64%
“…We know that the identity of the participants in both plant-microbe and plant-insect interactions are important factors in the outcomes of those interactions and their evolution (Bezemer et al 2014;Simon et al 2015;Bennett et al 2016). In tripartite interactions, the identity of all three interacting species is important and may influence the results of interactions (Bennett et al 2009;Kempel et al 2013;Zytynska et al 2014;Parker et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The number of exotic plants has increased steadily during contemporary times and these plants are a pervasive feature of most communities (Maron and Vilà 2001;Orians and Ward 2010), with profound and often devastating effects on native species and ecosystem functions (Vitousek et al 1987;Lovich 1996;Bezemer et al 2014). Multiple theories have been proposed to explain what makes some plants successful invaders while others fail to establish, including the Enemy Release Hypothesis (ERH) and the Biotic Resistance Hypothesis (BRH).…”
Section: Introductionmentioning
confidence: 99%